2014
DOI: 10.1007/s00484-014-0941-2
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal temperature range and short-term mortality in large US communities

Abstract: Research has shown that diurnal temperature range (DTR) is significantly associated with mortality and morbidity in regions of Asia; however, few studies have been conducted in other regions such as North America. Thus, we examined DTR effects on mortality in the USA. We used mortality and environmental data from the National Morbidity Mortality Air Pollution Study (NMMAPS). The data are daily mortality, air pollution, and temperature statistics from 95 large US communities collected between 1987 and 2000. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 54 publications
5
31
1
Order By: Relevance
“…Furthermore, the authors suggest that an inflammatory nasal responses (Graudenz et al 2006) may result from sudden temperature changes. In this study, we found a small negative effect of DTR with increasing mortality at higher ranges (models adjusted for temperature) which correspond well with findings from other studies (Lim et al 2013; Lim et al 2014). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the authors suggest that an inflammatory nasal responses (Graudenz et al 2006) may result from sudden temperature changes. In this study, we found a small negative effect of DTR with increasing mortality at higher ranges (models adjusted for temperature) which correspond well with findings from other studies (Lim et al 2013; Lim et al 2014). …”
Section: Discussionsupporting
confidence: 92%
“…We hypothesised that diurnal changes in temperature are causing increases in mortality. Several recent studies have established a relationship between temperature and DTR in Asia and North America (Lim et al 2013; Lim et al 2012; Lim et al 2014; Ding et al 2015; Kan et al 2007). In Bangladesh, DTR shows a strong seasonal pattern with the highest ranges observed during the cold season and is highly correlated with temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diurnal temperature range (DTR, i.e., the intra-day temperature change) is a well-known risk factor of weather-related human health. Numerous studies have described a positive association between DTR and mortality (Cao et al 2009;Lim et al 2015;Tam et al 2009;Vutcovici et al 2014;Yang et al 2013a), and have reported that people who are elderly, less educated, female or have cardiovascular or respiratory disease are more susceptible to DTR than others (Kan et al 2007b;Lim et al 2012a;Yang et al 2013b). In addition, because the DTR has been reported as an important meteorological indicator closely related with global climate change (Braganza et al 2004;Kan et al 2007b;Yang et al 2013b), an in-depth investigation of the DTR-mortality relationship becomes important as it helps to assess the future health impact of climate change more comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of annual mean TDN indicate that the short‐time temperature variation is more severe in high latitude and altitude areas than those in low latitude and altitude areas. Meanwhile, another intra‐day indicator of temperature variation called diurnal temperature change (DTR; Lim et al , ; ; Zhou et al , ), which can be calculated as the maximum temperature subtracted by the minimum temperature within 1 day, is available. DTR is high in low latitudes for relatively large solar elevation angle changes within a day (Braganza et al , ; Shahid et al , ).…”
Section: Resultsmentioning
confidence: 99%